Pretagogia: construindo um referencial teórico-metodológico de matriz africana para a formação de professores/as - Silva, Geranilde Costa e (2013)
In 2003, the federal government approved Law No. 10,639 , thus instituting the teaching of African History and Culture and african - Brazilian basic education and higher education ( public and private) from all over the country. In order to contribute towards the implementation of that law is that the doctoral studies did an intervention research seeking to build a theoretical and methodological framework of African origin to develop teacher training / as . This framework was named Pretagogia : pedagogy black to black and white. The Pretagogia sits on the values of the African worldview, which is ancestrally, oral tradition, the body as spiritual source and producer of knowledge, appreciation of nature, religion , the notion of territory and the principle of circularity. Promoted this research along to a public school in Fortaleza, together with teachers from Kindergarten and Primary Education I. This study had the following steps: 1st - Formation of the theoretical and methodological basis of African origin: the Pretagogia; 2nd - development of training / the educators / as through Pretagogia, prompting educators to have contact with african literary reference - Brazilian, participation in workshops dealing with the History and culture African, Afro -Brazilian and Afro - Ceará, as well as visits to places recognizably linked to black culture , such as: yard candomblé . At the end of the training the group of educators reached the following findings: a) who ignored history and African culture and african - Brazilian b ) recognized the fallacy of racial democracy, and thus the existence of racism c ) perceive their experiences and most intimate memories with blackness, and realized the invisibility was given to the subject of blackness, d) is assumed as a descendant of African peoples and thus started to value the principles of the African worldview, and ) prejudices that had demystified umbanda and candomblé against, and finally managed to create educational material geared to the study and appreciation of African history and culture and african - Brazilian . At the end of this study it was possible to say that the Pretagogia while theoretical and methodological framework of African origin could realize promote teacher training / leading the group of teachers felt the participants in the african - Brazilian culture and imbued with the desire to build a non-racist education.